A Study of Ransomware Attacks: Evolution and Prevention - Aini Khalida Muslim; Dzunnur Zaily Mohd Dzulkifli; Mohammed Hayder Nadhim; Roy Haizal Abdellah (Journal of Social Transformation and Regional Development, 2019)
Ransomware is a combination of two words, ransomware and software. In other words, ransomware makes it really hard forusers to access all files and data in a computer because it hacks the data and do not allow the users to access the files unless theypay ransom to the hacker. Dr. Joseph Popp is the first person to develop ransomware. Ransomware is known as a global epidemic that attacks all types of organizations using computing infrastructure. Ransomware has undergone various evolutions. Preventive measuresare needed in order to avoid losses especially in business. The purpose of this study is to examine the evolution of ransomware and preventionsagainst it. In this study, the secondary data were collected by using telemetry data by Symantec to track ransomware attacks in certain countries. Samplescame from among top 5 countries that have been declared as the onesmostly infected by Crypto Ransomware and Locker Ransomware infections. The findings of the study confirm that ransomware prevention is really needed in order to avoid the countries from beingcontinuously attacked by Ransomware. The findings in this study can be used as a reference for future researchers who want to conduct further study especially on cybercrimes